COMPARATIVE ANALYSIS OF CLINICAL CHRONIC BACTERIAL PROSTATITIS IN PATIENTS WITH DEFICIENCY AND NORMAL TESTOSTERONE LEVELS - A. A. Chernyj; M. I. Kogan; H. S. Ibishev (Вестник урологии)
The study included a survey of 42 patients with chronic bacterial prostatitis. Depending on the level of total testosterone, patients were divided into two groups : I group – 20 patients whose serum total testosterone was below the standard ratio (8-12 nmol/l), II group – 22 patients in whom testosterone matched normative range (> 12 nmol/l). The analysis of the study showed that patients with chronic bacterial prostatitis on a background of testosterone deficiency recorded more severe manifestations of infection in the prostate, as revealed by clinical, laboratory and instrumental investigations. In summary provided material, a comparative analysis of the clinical course of chronic bacterial prostatitis against testosterone deficiency showed more severe changes in the prostate in patients with total testosterone below 8 nmol/l.